2009
DOI: 10.1007/s00270-009-9711-7
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Randomized Study of Doxorubicin-Eluting-Bead Embolization in the Treatment of Hepatocellular Carcinoma: Results of the PRECISION V Study

Abstract: Transcatheter arterial chemoembolization (TACE) offers a survival benefit to patients with intermediate hepatocellular carcinoma (HCC). A widely accepted TACE regimen includes administration of doxorubicin-oil emulsion followed by gelatine sponge—conventional TACE. Recently, a drug-eluting bead (DC Bead®) has been developed to enhance tumor drug delivery and reduce systemic availability. This randomized trial compares conventional TACE (cTACE) with TACE with DC Bead for the treatment of cirrhotic patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

50
1,111
16
35

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 1,383 publications
(1,212 citation statements)
references
References 33 publications
50
1,111
16
35
Order By: Relevance
“…8 Clinical studies have shown that DEB loaded with doxorubicin has a safe pharmacokinetic profile with lower systemic drug exposure and significantly reduced liver toxicity compared with conventional TACE. [9][10][11] Despite these advances and technical refinements, the long-term survival of patients managed with TACE are not fully satisfactory, mainly as a result of the high rates of tumor recurrence. TACE exerts therapeutic effects only in the treated territory; thus other HCC undetected at the time of the procedure may progress or new tumors may develop.…”
Section: Introductionmentioning
confidence: 99%
“…8 Clinical studies have shown that DEB loaded with doxorubicin has a safe pharmacokinetic profile with lower systemic drug exposure and significantly reduced liver toxicity compared with conventional TACE. [9][10][11] Despite these advances and technical refinements, the long-term survival of patients managed with TACE are not fully satisfactory, mainly as a result of the high rates of tumor recurrence. TACE exerts therapeutic effects only in the treated territory; thus other HCC undetected at the time of the procedure may progress or new tumors may develop.…”
Section: Introductionmentioning
confidence: 99%
“…(19) A comprehensive understanding of updated efficacy and safety data of lipiodol TACE in the treatment of HCC is important, especially considering that alternate options for regional hepatic tumor treatment-including arterial embolization with drug-eluting beads and internal radiation with yttrium-90 microspheres-have been proposed and are currently undergoing clinical investigation. (20,21) Therefore, we performed a systematic literature review of the available evidence on the efficacy and safety of lipiodol TACE in treatment of HCC.…”
mentioning
confidence: 99%
“…Transarterial chemoembolization has become a commonly employed treatment for HCC (9)(10)(11). However, hepatic dysfunction is frequently observed after chemoembolization (12,13).…”
mentioning
confidence: 99%